ENHANCEMENT OF GENERIC SCIENCE SKILLS OF ATRO BANDA ACEH STUDENTS ON RESPIRATORY SYSTEM ANATOMICAL MATERIALS WITH REMOTE ASSIGNMENT METHOD - Febriyanti, Dewi; Hasanah, Mauizah (Jurnal Biologi Sains dan Kependidikan, 2021)
The purpose of this study was to determine the improvement of generic skills in problem solving science and learning and technology of ATRO Banda Aceh students on the anatomy and physiology of the respiratory system. The method used in this study is a pre-experimental design using a one group pretest-posttest research design. The population in this study were 46 people with a sample of 30 people, the sample selection was done by purposive sampling. The results of the study using t-test analysis with the pretest results of students being 70.8, while the posttest average value of 78.9 showed an increase in students' generic science skills after the learning process. The conclusion of this study shows that using the distance method can also improve students' generic science skills. It is hoped that there will be further research on improving generic science skills using a visual laboratory as a support for online learning.Keywords: keterampilan generik sains, pretest, posttes